ANALISIS PERANCANGAN SISTEM INFORMASI AKUNTANSI PENGGAJIAN PADA YAYASAN MASJID NURUL HUDA JATIWARINGIN - Dwi Puspita Agustin (Jupiter: Journal of Computer & Information Technology, 2020)
This research was conducted at Yayasan Masjid Nurul Huda Jatiwaringin which is an institution that moves in the education field. The purpose of this study is to find out and evaluate the payroll accounting information system that is running on the Yayasan Masjid Nurul Huda Jatiwaringin and to provide an alternative design of payroll accounting information system at Yayasan Masjid Nurul Huda Jatiwaringin. The data used in this study are primary data obtained directly from the Nurul Huda Mosque Foundation Jatiwaringin and secondary data obtained in the form that is already in the form of publication. The analytical tool used in this research is a qualitative descriptive analysis tool by conducting system analysis, which then proceeds with a conceptual design sketch by designing a flowchart, Data Flow Diagram (DFD), Entity Relationship Diagram (ERD), and Normalization. After that proceed to the physical design stage but only limited to the design of database design, input and output design. Based on the results of the study the authors found that the salary system run by the foundation is less effective because there is still a double task on the treasurer, and also the document sheet used still does not meet the needs of the system. In addition, the absence of authorization activities of employee attendance list performed by the timekeeping function and outgoing cash proof documents has not been authorized by the accounting function. Furthermore, the authors designed a payroll accounting information system that is able to overcome the weaknesses and shortcomings.